Disease reclassification risk with stringent criteria and frequent monitoring in men with favourable‐risk prostate cancer undergoing active surveillance. (4th July 2015) - Davis, John W.; Ward, John F.; Pettaway, Curtis A.; Wang, Xuemei; Kuban, Deborah; Frank, Steven J.; Lee, Andrew K.; Pisters, Louis L.; Matin, Surena F.; Shah, Jay B.; Karam, Jose A.; Chapin, Brian F.; et al.
Abstract : Objectives: To determine the frequency of disease reclassification and to identify clinicopathological variables associated with it in patients with favourable‐risk prostate cancer undergoing active surveillance (AS). Patients and Methods: We assessed 191 men, selected by what may be the most stringent criteria used in AS studies yet conducted, who were enrolled in a prospective cohort AS trial. Clinicopathological characteristics were analysed in a multivariate Cox proportional hazards regression model. Key features were an extended biopsy with a single core positive for Gleason score (GS) 3 + 3 (<3 mm) or 3 + 4 (<2 mm) and a prostate‐specific antigen (PSA) level <4 ng/mL (adjusted for prostate volume). Biopsies were repeated every 1–2 years and clinical evaluations every 6 months. Disease was reclassified when PSA level increased by 30% from baseline, or when biopsy tumour length increased beyond the enrolment criteria, more than one positive core was detected or any grade increased to a dominant 4 pattern or any 5 pattern. Results: Disease was reclassified in 32 patients (16.8%) including upgrading to GS 4 + 3 in five patients (2.6%). The median (interquartile range) follow‐up time among survivors was 3 (1.9–4.6) years. Overall, 13 of the 32 (40.6%) had incremental increases in GS. Tumour length (hazard ratio 2.95, 95% confidence interval [CI] 1.34–6.46; P = 0.007) and older age (hazard ratio 1.05, 95% CI 1.00–1.09; P = 0.05) were identified as significant and marginally significant predictors of disease reclassification, respectively. Disease remained stable in 83.2% of patients. Conclusion: The need persists for improvements in risk stratification and predictive indicators of cancer progression.